2014
DOI: 10.1007/s00421-014-2967-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isometric training on the knee extensor moment–angle relationship and vastus lateralis muscle architecture

Abstract: Isometric training at specific knee angles led to significant shifts of peak torque in the direction of the training muscle lengths. The greater strength gains and the architectural changes with training at long muscle lengths probably come from a combination of different factors, such as the different mechanical stresses placed upon the muscle-tendon complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
108
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(127 citation statements)
references
References 40 publications
13
108
2
1
Order By: Relevance
“…Recently, it has been reported that 8 weeks of isometric knee extension training at long muscle length induced greater strength gains compared to training at short muscle length [5]. However, although muscle thickness was increased similarly between groups, fascicle length was not altered after the two training interventions [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, it has been reported that 8 weeks of isometric knee extension training at long muscle length induced greater strength gains compared to training at short muscle length [5]. However, although muscle thickness was increased similarly between groups, fascicle length was not altered after the two training interventions [5].…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies aimed to investigate whether training at different muscle lengths of the knee extensors induces different muscle strength and mass adaptations [5][6][7][8]. Recently, it has been reported that 8 weeks of isometric knee extension training at long muscle length induced greater strength gains compared to training at short muscle length [5].…”
Section: Introductionmentioning
confidence: 99%
“…1). These curves have been successfully reproduced in human dynamics as the angle-torque-velocity relationship using force transducers or isokinetic devices [24][25][26][27][28][29][30][31][32] . The angle-torque relationship is commonly explained in text books stating that the relative positions of the actin and myosin filaments change as the muscle contracts with the number of effective cross-bridges decreased or optimized 34) .…”
Section: Constant Length or Speed Trainingmentioning
confidence: 99%
“…The curvature of the angle-torque-velocity relationship can be altered by training, however the adaptive changes are specific to training 30,31,36) . It has been well documented that after weeks of isometric or isokinetic training, the strength gain is most promising at the joint angle or velocity of training, with "a transfer of strength gain" being possible near the joint angle or velocity at which the training has been undertaken 5,25,[30][31][32][36][37][38] .…”
Section: Constant Length or Speed Trainingmentioning
confidence: 99%
See 1 more Smart Citation